Development for managers and sales staff - McNelly, Hunter (My University, 2025)
Employees, managers, and companies find themselves always looking for good, developed talent that can move their business forward. Unfortunately, this tends to lend themselves to pass over internal candidates and look externally for top tier talent. While this does work sometimes, it does not move a business forward quickly and puts the company susceptible to losing their own good talent. This is where employee development plans are advantageous for not only companies, but employees as well. Development plans are customizable, and adaptable based on positions, personnel, personalities, and companies. However, the need for them in every dealership does not change. While each employee has different motivation factors, and each company has different values, guiding principles, and mission statements, the need to grow and move the business forward while developing yourself as an employee and keeping your team engaged and motivated as a manager is apparent. Development plans are a framework and a tool to challenge employees and teams, while opening a structured conversation so both parties can understand where they are currently and what capabilities they need to contribute effectively to where the business is headed. Whether you are a sales professional, service manager, or parts manager within a dealership, you must have a certain set of baseline and competency skills to be successful. This thesis outlines what a development plan is, the importance of a development plan, and showcases what can be achieved when a correct development plan is implemented across a company.
Keywords: Employee development; Agriculture dealership; Talent development; Development plan